Wiener and Hyper-Wiener Indices of Polygonal Cylinder and Torus. (9th April 2021) - Peng, Zhi-Ba; Nizami, Abdul Rauf; Iqbal, Zaffar; Munir, Muhammad Mobeen; Waqar Ahmed, Hafiz Muhammad; Liu, Jia-Bao
Abstract : In this study, we first introduce polygonal cylinder and torus using Cartesian products and topologically identifications and then find their Wiener and hyper-Wiener indices using a quick, interesting technique of counting. Our suggested mathematical structures could be of potential interests in representation of computer networks and enhancing lattice hardware security.